Economic-Demographic Interactions in Agricultural Development: The Case of Rural-to-Urban Migration - Oded Stark (Food and Agriculture Organization of The United Nations (FAO), 1978)
The purpose of this study is to present a new piece of conceptual work which analyzes rural-to-urban migration and, in the light of this conceptual work, to examine: (a) some of the migration-related evidence; (b) interactions between rural-to-urban migration and some other key variables; (c) relevant policy implications. The main focus of the study is the interactions between rural-to-urban migration of labour and a number of development variables - namely technological change in agricultural production, income distribution by size, distribution and level of unemployment, fertility behaviour - as well as some other variables. The study concludes by referring to the policy implications emanating from the analysis of these interactions. Perhaps the most striking conclusion emerging from the analysis is that in light of the various benefits and the not unfavourable side (net) effects (both private and social) generated by rural-tourban migration, some of the most frequently expressed concerns accompanying it are groundless. Moreover, many of the policy recommendations prescribed to reduce or eliminate it are unnecessary, irrelevant and unlikely to be effective. The study is organized around an explicit (and novel) analytical construct which is, in particular, a less-developed-economy agriculture-specific construct. (...)
Keywords: D13; D14; D31; D81; D86; J43; J61; O12; O15; Q12; Q14; R23; 330; Rural-to-urban migration; Agricultural development